Anti-Sustainability Narratives in Chat Apps: What Shapes the Brazilian Far-Right Discussion About Socio-Environmental Issues on WhatsApp and Telegram - Rose Marie Santini; Débora Gomes Salles; Marina Loureiro Santos; Luciane Leopoldo Belin; Thiago Ciodaro (Journalism and Media, 2025)
This study examines how socio-environmental issues are framed and disseminated in far-right WhatsApp and Telegram groups in Brazil. By collecting and analyzing over 87,962 messages shared from 2023 to 2024, we identify how the sustainability agenda is instrumentalized to deepen political polarization. Using a mixed-methods approach guided by a theoretical–methodological perspective in framing theory, we applied topic modeling to identify key themes and conducted qualitative analysis to categorize hyperlinked sites shared by group participants. The results suggest that environmental discussions in these groups are often intertwined with broader cultural war narratives and economic interests, particularly agribusiness. Disinformation, conspiracy theories, and attacks on environmental policies, activists, and NGOs are common strategies used to reinforce the salience of frames that undermine sustainability efforts. This study highlights the role of chat apps in facilitating the spread of anti-environmental narratives due to their decentralized and encrypted nature. Additionally, the findings suggest that hyperlinking practices within these groups can be understood as a framing strategy that contributes to the legitimization of misleading narratives by repeatedly circulating information from biased or unreliable sources.